Association Between Serum Insulin-Like Growth Factor 1 Levels and the Clinical Symptoms of Chronic Schizophrenia: Preliminary Findings - Okamoto, Naomichi; Yoshino, Koji; Kitagawa, Shogo; Fujii, Rintaro; Hamada, Shinsuke; Ikenouchi, Atsuko; Konishi, Yuki; Ueda, Nobuhisa; Eto, Yoshinori; Tsutsumi, Yasunari; Yoshimura, Reiji (Frontiers in Psychiatry, 2021)
Purpose: Insulin-like growth factor 1 (IGF-1) is a trophic mediator that is regulated by growth hormone and associated with the proliferation, development, and growth of neural cells. IGF-1 may be associated with the pathophysiology of schizophrenia, but this association remains controversial. This study aimed to investigate the relationship between serum IGF-1 levels and psychiatric symptoms in patients with chronic schizophrenia. Patients and Methods: A total of 65 patients were recruited from the University of Occupational and Environmental Health, Komine Eto Hospital, Moji Matsugae Hospital, Shin-Moji Hospital, and Tsutsumi Hospital in Kitakyushu between September 2019 and June 2020. Further, 20 healthy age- and sex-matched control participants were recruited from the Komine Eto Hospital and the University of Occupational and Environmental Health. Patients with schizophrenia were assessed using the Positive and Negative Syndrome Scale (PANSS) and the Drug-Induced Extrapyramidal Symptoms Scale. Serum levels of free plus albumin-bound IGF-1 (IGF-1) were measured by immunoradiometric assay. The measurements were performed using antibody beads for bound/free separation. Associations between serum IGF-1 levels and the PANSS scores were determined. We also examined the associations between serum IGF-1 levels and diabetes, antipsychotic drug use, and disease duration. Results: No significant difference was found in the serum IGF-1 level between patients with schizophrenia and healthy controls. Serum IGF-1 levels were significantly negatively correlated with the PANSS total score (R2 = 0.06, p = 0.015) and PANSS general score (R2 = 0.088, p = 0.008), but not with the PANSS positive scores and PANSS negative scores. Serum IGF-1 levels were not related to the prevalence of diabetes (p = 0.64). However, a significant correlation was observed between serum IGF-1 levels and age (B = −1.88, p < 0.0001). Serum IGF-1 levels could not distinguish patients with schizophrenia and healthy controls. Conclusion: The association between serum IGF-1 levels and psychiatric symptoms may be complicated in patients with chronic schizophrenia.